Treating Intracranial Abscesses in Rats with Stereotactic Injection of Biodegradable Vancomycin-Embedded Microparticles - Yuan-Yun Tseng; Ching-Wei Kao; Kuo-Sheng Liu; Ya-Ling Tang; Yen-Wei Liu; Shih-Jung Liu (Pharmaceutics, 2020)
Brain abscesses are emergent and life-threating despite advances in modern neurosurgical techniques and antibiotics. The present study explores the efficacy of vancomycin embedded to 50:50 poly(lactic-co-glycolide acid) (PLGA) microparticles in the treatment of brain abscess. The vancomycin embedded microparticles (VMPs) were stereotactically introduced into the cerebral parenchyma in Staphylococcus aureus bacteria- induced brain abscess-bearing rats. Experimental rats were divided into three groups: group A (n = 13; no treatment), group B (n = 14; daily vancomycin injection (5 mg intraperitoneally), and group C (n = 12; stereotactic introduction of VMPs into the abscess cavity). Group C exhibited no inflammatory response and significantly increased survival and reduced mean abscess volumes (p <0.001) at the eighth week, compared with other groups. Vancomycin delivery via a biodegradable PLGA vehicle can easily attain Area Under the Curve (AUC)/minimum inhibitory concentration (MIC) ratios of ≥400, and strengthens the therapeutic efficacy of antibiotics without provoking any potential toxicity. Biodegradable VMPs are a safe and sustainable drug delivery vehicle for the treatment of brain abscess.